A Comprehensive Approach to Voice of Customer Extraction: A Case of Product Development for Smart Washing Machine - Im, Youngjae; Kim, Seokhyeon; Jaein Lee (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
While customers in the past were satisfied with products that met basic functional needs, contemporary users increasingly expect enriched experiences throughout their interactions with products and services. To address this shift, organizations are adopting customer experience frameworks aligned with human factors and ergonomics, emphasizing usability, satisfaction, and system-level performance. The Voice of the Customer (VoC) has become a critical input for capturing user requirements and informing experience-centered design. This study proposes a structured process for systematically collecting VoC related to holistic user experiences and evaluates its applicability through a case study involving a consumer appliance. Fifteen participants performed real-world tasks with a washing machine, enabling the identification of fine-grained user activities—such as IoT application control and mid-cycle laundry insertion—not documented in prior research. The process also elicited novel forms of user feedback that had previously been overlooked. As products become increasingly complex and feature-rich, accounting for diverse user interactions is essential for advancing both usability and safety. The proposed VoC collection process provides a practical contribution to human-centered product and service development, supporting the integration of ergonomic considerations for the enhancement of overall user experience.